Neural processing of disorder-related stimuli in patients with anorexia nervosa: a narrative review of brain imaging studies - Simon, Joe J.; Stopyra, Marion A.; Friederich, Hans-Christoph (Journal of Clinical Medicine, 2019)
Abnormalities and alterations in brain function are commonly associated with the etiology and maintenance of anorexia nervosa (AN). Different symptom categories of AN have been correlated with distinct neurobiological patterns in previous studies. The aim of this literature review is to provide a narrative overview of the investigations into neural correlates of disorder-specific stimuli in patients with AN. Although findings vary across studies, a summary of neuroimaging results according to stimulus category allows us to account for methodological differences in experimental paradigms. Based on the available evidence, the following conclusions can be made: (a) the neural processing of visual food cues is characterized by increased top-down control, which enables restrictive eating, (b) increased emotional and reward processing during gustatory stimulation triggers disorder-specific thought patterns, (c) hunger ceases to motivate food foraging but instead reinforces disorder-related behaviors, (d) body image processing is related to increased emotional and hedonic reactions, (e) emotional stimuli provoke increased saliency associated with decreased top-down control and (f) neural hypersensitivity during interoceptive processing reinforces avoidance behavior. Taken together, studies that investigated symptom-specific neural processing have contributed to a better understanding of the underlying mechanisms of AN.